Comprehensive mapping of molecular cytogenetic markers in pitaya (Hylocereus undatus) and related species - Harun, Arrashid; Song, Shipeng; You, Xixi; Liu, Hui; Wen, Xiaopeng; Fang, Zhongming; Cheng, Zhihao; Chen, Chunli (Frontiers in Plant Science, 2024)
Pitaya (Hylocereus undatus; 2n=22) is an important fruit crop from the Cactaceae family, originally domesticated in Mexico and the USA, and is now widely cultivated for its nutritional benefits. It is characterized by its distinctive triangularshaped stems and large, showy flowers, thriving in arid and semi-arid environments, particularly in hot, dry climates. However, systematic chromosomal studies, including chromosomal mapping of cytogenetic markers in pitaya, are limited, presenting challenges for its cytogenetic improvement. To address this issue, we designed oligobarcodes specific to thirty-three chromosome regions based on the pitaya reference genome and applied them to both pitaya and cactus (Selenicerus grandifloras; 2n=22) for oligo-barcodes mapping, karyotyping, and chromosome identification. We utilized FISH technology, employing oligo, rDNA, and tandem repeat probes for chromosomal mapping, identification, and karyotyping of pitaya and related species.We successfully localized oligo-barcodes on eleven pairs of chromosomes in both pitaya and cactus, demonstrating the effectiveness of the synthesized oligo-barcodes.We used two ribosomal DNA (rDNA) probes (45S and 5S) and two tandem repeat probes (GTR11 and STR3) in pitaya (both diploid and tetraploid) and two other Cactaceae species (S. grandifloras and Opuntia humifusa; 2n=40) for chromosomal mapping. The analysis of rDNA distribution and CMA (Chromomycin A3) banding across different chromosomes in pitaya and cacti highlights the concept of conserved rDNA. This study provides fundamental insights into cytogenetic markers and their localization across different chromosomes in pitaya and other Cactaceae species.